2013
DOI: 10.1093/jeg/lbt020
|View full text |Cite
|
Sign up to set email alerts
|

The effect of agglomeration size on local taxes

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 26 publications
3
11
0
Order By: Relevance
“…Buettner (2001) finds that more populous German municipalities set higher local business tax rates, and Charlot and Paty (2006) find that French municipalities with greater market potential do likewise. 7 More recently, the reverse-causation problem has been addressed by instrumenting the right-hand-side agglomeration measure with agglomeration measured at a date prior to the introduction of the tax that represents the left-hand-side variable (Jofre-Monseny, 2013; Koh, Riedel and Böhm, 2013;and Luthi and Schmidheiny, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Buettner (2001) finds that more populous German municipalities set higher local business tax rates, and Charlot and Paty (2006) find that French municipalities with greater market potential do likewise. 7 More recently, the reverse-causation problem has been addressed by instrumenting the right-hand-side agglomeration measure with agglomeration measured at a date prior to the introduction of the tax that represents the left-hand-side variable (Jofre-Monseny, 2013; Koh, Riedel and Böhm, 2013;and Luthi and Schmidheiny, 2014).…”
Section: Introductionmentioning
confidence: 99%
“… In a related strand of recent research, Charlot and Paty (2007), Jofre‐Monseny and Solé‐Ollé (2010, 2012), Koh and Riedel (2010), Jofre‐Monseny (forthcoming) and Lüthi and Schmidheiny (2011)) have found that local tax rates are positively correlated with measures of local agglomeration. …”
mentioning
confidence: 99%
“…Tax competition is constrained by agglomeration effects, since localities in economic clusters will be able to exert higher taxes compared to localities in the periphery. Luthi and Schmidheiny (2011) provide evidence regarding agglomeration effects on taxes in Swiss municipalities. They report that tax competition between regions is weak, but tax competition within regions is much stronger.…”
Section: Fd and Tax Competitionmentioning
confidence: 99%